V.V. Davydov's Ideas in Education: The Past and the Present - Egorenko T.A; Sanina S.P (Moscow State University of Psychology and Education, 2020)
The article presents an analysis of the main conceptual ideas of the scientific school of V.V. Davydov. One of the main vectors of ideas is devoted to the formation of theoretical thinking and consciousness in children, which are the basis of a person's cultural orientation in contemporary reality. The article outlines some examples of implementation of these ideas in primary school. The key theme is the promotion of V.V. Davydov's ideas by his student, professor V.A. Guruzhapov. The article presents his 'didactic assumptions' about how education should be organized. The first shows that everything that has ever been created by people as a result of a creative impulse, a discovery about the essence of the phenomena of the surrounding world, can then be understood by other people as well. The second is that it is possible to construct artificial conditions in which a person begins to understand what people once discovered about the essence of the surrounding reality. The article also analyzes the process of setting the learning task. The second vector focuses on the issue of training teachers for modern school who would be able to implement the ideas of developmental teaching.